Immunofluorescence Confocal Laser Scanning Microscopy and immuno-electron microscopic identification of keratins in human maternofetal interaction zone. - Ahenkorah, J.; Hottor, B.; Byrne, S.; Bosio, P.; Ockleford, C.D. (My University, 2009)
We show here that at least 5 keratin proteins are present in villous trophoblast and the same 5 in extravillous trophoblast. A further 14 tested were undetectable in these tissues. In contrast, 10 of the 19 keratins tested were present in amniotic epithelium. The marking of amniotic epithelium on the one hand, as distinct from villous and extravillous trophoblast on the other, can be achieved using 5 keratins (K4, 6, 13, 14 and 17) with a mixture of positive and negative discrimination that is expected, in combination, to be highly sensitive. All the specific keratins identified in trophoblast were apparently up-regulated on the pathway to extravillous trophoblast. Co-ordinated differentiation at the molecular expression level is indicated by this finding. The relevant keratins are K5, 7, 8, 18 and 19. Specific keratins have been identified that are down-regulated in villous trophoblast in pre-eclamptic pregnancy. This difference between healthy and pre-eclamptic chorionic villous trophoblast keratin expression was statistically significant in 4 out of the 5 keratins. This was not the case for the extravillous trophoblast at the immunofluorescence confocal level but significant differences were obtained using immunogold electron microscopy. We suggest that the villous trophoblast in pre-eclamptic placentae is cytoskeletally weaker with respect to the filaments made from these specific proteins and that this is one reason why, in pre-eclampsia, trophoblast is deported in greater quantity than in healthy placentae.